2012
DOI: 10.3144/expresspolymlett.2012.98
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ionic liquids on the dielectric relaxation behavior of CNT based elastomer nanocomposites

Abstract: Abstract. The influence of an imidazolium type ionic liquid (IL) on the relaxation behavior of carbon-nanotube (CNT) based polychloroprene nanocomposites prepared by melt mixing has been investigated by broadband dielectric spectroscopy. It is demonstrated that the presence of the ionic liquid modifies the relaxation behavior of the pure rubber matrix and leads to a significant increase of the conductivity for the CNT/rubber composites. For the unfilled rubber, a distinct glass transition of the IL is observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…[8,9,10,11] In later work on ILCNTs/CR composites, Subramaniam et al reported that combining CR with ionic liquid modified CNTs causes an enhancement in thermal stability, which can be attributed to the fine dispersion of the modified tubes in the CR matrix. [12] In other investigations, the electrical conductivity of IL-CNTs/CR composites increased upon accelerated thermal aging, and therefore, the authors concluded that these composites may be useful for applications where conductivity at elevated temperatures is required.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9,10,11] In later work on ILCNTs/CR composites, Subramaniam et al reported that combining CR with ionic liquid modified CNTs causes an enhancement in thermal stability, which can be attributed to the fine dispersion of the modified tubes in the CR matrix. [12] In other investigations, the electrical conductivity of IL-CNTs/CR composites increased upon accelerated thermal aging, and therefore, the authors concluded that these composites may be useful for applications where conductivity at elevated temperatures is required.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of ionic liquids to functionalise and improve the dispersion of carbon nanotubes has been intensively studied [9,10] also in diene elastomers [11]. Ionic liquids resulted in the development of a conductive polychloroprene rubber containing a low concentration of multi-walled carbon nanotubes (MWCNTs) [12,13]. The fine homogeneous dispersion of the MWCNTs and their strong secondary network in the elastomer resulted in the high conductivity of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (BmiTFSI) was used to develop conducting composite of multi-walled carbon nanotubes (MWCNTs) and polychloroprene rubber [12,16]. The cation-p interactions between the BmiTFSI and tubes resulted in uniform dispersion of MWCNTs and the formation of their percolating network, which significantly increased the conductivity of the rubber composite.…”
Section: Introductionmentioning
confidence: 99%